Photoperiod in aquaculture of the sea urchin Arbacia dufresnii (Echinodermata: Echinoidea): Effects on gamete production and maturity - Sepúlveda, Lucas-R. (2021)
Introduction: Photoperiod is, together with temperature and food availability, one of the main stimuli in the regulation of gametogenesis in a wide variety of species. Objective: To evaluate the effect of photoperiod on the production of mature gametes in cultured Arbacia dufresnii. Methods: An experiment was carried out with three varying light-dark regimes/treatments: constant light (24 h light), neutral photoperiod (12 h light, 12 h darkness), and constant darkness (24 h darkness). Twenty females were used in each treatment. All were induced to spawn and, ten randomly selected females from each treatment were induced to spawn again after 30 days. After 60 days, spawning was induced in the remaining females. The gametes were collected in filtered seawater, fixed in Davidson solution, quantified and measured per individual in triplicate in a Sedgewick-Rafter chamber. To determine maturation, fertilization success was evaluated 30 minutes after fertilization. Results: Our results showed that in the aquaculture system, after only two months, mature gametes were obtained, and in the neutral light regime there were 10 times more gametes than the number produced in wild sea urchins during the spawning period in question. We also found that with a greater exposure to light, a lower number of mature gametes was produced. Conclusions: This study suggests the viability of the production of mature gametes in a short period of time as regards Arbacia dufresnii.